2021
DOI: 10.4314/sokjvs.v18i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and management of aspergillosis in some poultry farms in Jos metropolis, Nigeria

Abstract: Aspergillosis is important in poultry production and human health but difficulty in its ante mortem diagnosis in addition to the  unsuccessful outcome of most management options has made the disease a lingering nightmare to farmers. This study presents the clinicopathological features and management of aspergillosis in some poultry farms in Jos metropolis, Nigeria. Thirteen cases of  aspergillosis from 12 poultry farms were confirmed and managed from April, 2019 to March, 2020 with 7.6% cases in a mixed turkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Since the vaccination against AI is not officially permitted in Nigeria and local chickens are not usually vaccinated, according to the report Meseko et al (2020), the antibodies detected in these birds could only have resulted from seroconversion following natural infection with the viruses. Thus, the local chickens could serve as reservoirs shedding the virus into the environment, thereby playing a crucial role in the epidemiology of the disease which agrees with research carried out by Ameji et al (2020). This finding is also consistent with previous reports of infection with LPAI H5N8 in Jos Plateau State, Nigeria (Ameji et al, 2019) and other parts of the world such as China, Asia and Europe.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since the vaccination against AI is not officially permitted in Nigeria and local chickens are not usually vaccinated, according to the report Meseko et al (2020), the antibodies detected in these birds could only have resulted from seroconversion following natural infection with the viruses. Thus, the local chickens could serve as reservoirs shedding the virus into the environment, thereby playing a crucial role in the epidemiology of the disease which agrees with research carried out by Ameji et al (2020). This finding is also consistent with previous reports of infection with LPAI H5N8 in Jos Plateau State, Nigeria (Ameji et al, 2019) and other parts of the world such as China, Asia and Europe.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the detection of antibodies to low pathogenic avian influenza serotype A/H9 in local chickens indicates the presence of low pathogenic AIVs infection. Other subtypes causing highly pathogenic (HP) Avian Influenza particularly subtype H5 have often been reported in the study area and indeed Nigeria by previous researchers (Ameji et al, 2020). The findings of this research indicate the first report of the detection of H9 from local chickens in Jos Plateau after a deductive literature search.…”
Section: Discussionsupporting
confidence: 55%
“…Regarding the productive purpose of the birds, in the cases obtained in Costa Rica, a higher risk was observed in animals destined to reproduction and broilers, contrary to the Nigerian research made in clinically sick chickens, where the most affected were the layers and where serious economic losses occur in the growth stage and just before the start of production [ 38 ]. Regarding broilers, in a study which compared the effect of an experimental infection by A. fumigatus in a line of White Leghorns (layers) and a line of broilers, it was observed that the layers did not present mortality compared with the broilers, which presented a mortality greater than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of Aspergillus in the lungs, environment, surface, food, and litter of birds has implications for public health, the occupational health of farmworkers, and animal health and welfare [ 1 , 33 , 37 , 38 ]. Aspergillosis is a sapronotic disease, which means that the infection is acquired by inhalation or ingestion of conidia from a contaminated environment, which can cause respiratory signs in immunocompromised patients and an asthma-like allergic reaction in people exposed to high concentrations or people who are repeatedly exposed to this fungus [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation